2011
DOI: 10.1523/jneurosci.2206-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of the Glutamate Receptor Subunit GluK3 Controls Polarized Trafficking

Abstract: Kainate receptors (KARs) are widely expressed in the brain and are present at both presynaptic and postsynaptic sites. GluK3-containing KARs are thought to compose presynaptic autoreceptors that facilitate hippocampal mossy fiber synaptic transmission. Here we identify molecular mechanisms that underlie the polarized trafficking of KARs composed of the GluK3b splice variant. Endocytosis followed by degradation is driven by a dileucine motif on the cytoplasmic C-terminal domain of GluK3b in heterologous cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A stretch of three basic amino acids (RKR) has been recognized as being critical for the observed ER retention, and it has been demonstrated that the RKR motif causes ER retention when fused to proteins otherwise trafficked to the plasma membrane. Similar retention motifs have since been identified in the NMDA receptor subunit GluN1 (RRR) [ 18 , 19 ] and subsequently in the KAR subunits GluK1, GluK3, and GluK5 [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Mechanisms Of Assembly and Surface Expression Of Kainate mentioning
confidence: 73%
See 1 more Smart Citation
“…A stretch of three basic amino acids (RKR) has been recognized as being critical for the observed ER retention, and it has been demonstrated that the RKR motif causes ER retention when fused to proteins otherwise trafficked to the plasma membrane. Similar retention motifs have since been identified in the NMDA receptor subunit GluN1 (RRR) [ 18 , 19 ] and subsequently in the KAR subunits GluK1, GluK3, and GluK5 [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Mechanisms Of Assembly and Surface Expression Of Kainate mentioning
confidence: 73%
“…In addition, in COS-7 cells a substantial amount of GluK3b has been shown to be immaturely glycosylated, as evidenced by its endoglycosidase H sensitivity. By contrast, GluK3b carrying a mutated dileucine motif was not EndoH-sensitive, suggesting that the dileucine motif may also be involved in ER retention of GluK3b [ 22 ].…”
Section: Mechanisms Of Assembly and Surface Expression Of Kainate mentioning
confidence: 99%
“…4.1 protein isoforms are localized to distinct subcellular compartments, including axons (50,51), and may play distinct roles in localizing kainate receptors to presynaptic terminals, where they function as autoreceptors to regulate neurotransmitter release (52). GluK3-containing receptors require dendritic endocytosis for their polarized expression at presynaptic terminals (53), raising the possibility that specific 4.1 isoforms are important for axonal targeting of these receptors by regulating their endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Biotinylation Assays-Biotinylation experiments were performed essentially as described previously (36,38). COS-7 cells were transfected in 6-well plates (2 wells/condition) and were incubated 24 h post-transfection.…”
Section: Methodsmentioning
confidence: 99%